Logico-Semantic Relation in The World Health Organization’s Covid-19 Myth-Busters - Lia Maulia Indrayani; Ekaning Krisnawati; Edfan Juliansyah (Universitas Pasundan, 2023)
In delivering the contents of the World Health Organization’s Covid-19 Myth-busters, the creator realized clause complexes besides clause simplexes. This research focuses on analyzing logico-semantic relation of clause complex. Thus, it can reveal the creator’s intention in realizing the clause complexes when conveying the myth-busters to the people of the world. This research utilizes a qualitative-descriptive research method. There are 48 expansion relationships in the myth-busters. They include one elaboration relationship, 22 extension relationships, and 25 enhancement relationships. Enhancement is the most-realized clause relationship in the myth-busters. This means that the creator intended to convey complementary ideas in the clause complexes by referencing time, condition, reason, purpose, and cause related to managing misinformation about Covid-19.